Does Social Support and Burnout Matter? Effects of Role Conflict and Workload on Workplace Bullying: A Proposed Framework - Ladan,, Sahnun; Nordin, Norani; H.M, Belal (AJMS, 2017)
The prevalent and negative impact of workplace bullying has called the attentions of both practitioners and researchers to begin investigations on its causes and outcomes on the targets and perpetrators, and how to ameliorate it. Some of the possible reasons for bullying studied include leadership, job characteristic, organizational culture, and work environment. Despite these studies, few have attempted to investigate the influence of workload and role conflict on workplace bullying. Further, previous studies also indicated conflicting results, and the mechanism through which workload and role conflict influences workplace bullying are not adequately addressed. Therefore moderator and mediator variables are suggested. This paper proposes social support and burnout as potential moderator and mediator on the relationship between workload, role conflict and workplace bullying